Dentists' Awareness And Their Practices Towards Radiation Precaution In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
Background: The science of medicine and dentistry has relied heavily on X-rays since their inception. There are several uses for X-rays, ranging from therapeutic to diagnostic. The most common use could be in dentistry, where it can be used for everything from the straightforward identification of tiny fractures and early cavities to supporting more intricate operations like precise implant planning.The study aims: To analyze the current status of knowledge and practices among the dentists towards radiation precaution.Methods: This is a cross-sectional study based on a questionnaire related to knowledge and practice regarding radiation precaution of patients and dental staff from January to March 2024. The study sample included 325 dentists practicing in KSA. All dentists employed in public, semi-public, and private settings made up the target population.Results: Radiation precaution was known to 96.6% of dentists. However, 73.9% believed that dental X-rays are hazardous, and roughly 35% were aware of the ALARA (as low as reasonably attainable) approach. Digital image receptors were used by 63.6% of the individuals. More over 60% of them disregarded the position and distance regulation, and only 16.7% of them used a film holder. Seven was the median knowledge score [5, 9], and there was a statistically signiﬁcant difference according to dentist qualiﬁcation (P ¼ 0.007), dental radiation precaution continuous training (P < 0.0001), age (P ¼ 0.007) and years of experience (P ¼ 0.039). The median practice score was 5 [4, 6] and there was a statically signiﬁcance association according to workplace setting (P ¼ 0.001). There was a signiﬁcant positive relationship between knowledge score and practice score (r ¼ 0.24, P